Reconfiguring Islamic Tradition: Reform, Rationality, and Modernity by Samira Haj (Stanford, CA.: Stanford University Press, 2009. 284 pages.) (American Journal of Islam and Society, 2009)
The goal of this book “is to provide a way of conceptualizing the Islamic traditionthat is different from that proposed by conventional scholarship”(p. 6). The author wants to highlight howMuslims themselves view modernitybecause their own views have been overshadowed by western scholarshipand have problematized assumptions founded on the oppositionaldichotomies of modern versus traditional or secular versus sacred. Sheargues that a tradition is not simply the recapitulation of previous beliefs andpractices, but that each successive generation confronts its own particularproblems via an engagement with a set of ongoing arguments. Therefore, theauthor asserts, one effective way of addressing Islam is to approach it asMuslims do – as a discursive tradition embodied in the practices and institutionsof their communities.Haj intends to attain her goals and highlights these problems by analyzingthe work of two significant Muslim reformers: Muhammad ibn Abd al-Wahhab (1703-87) and Muhammad Abduh (1849-1905). Although theybelong to different historical periods and social settings, she feels that theirwork has inspired the two major strands of contemporary Islamic politicalthought. The former, an Arabian reformer, has often been referred to as the“legendary mastermind of a ‘fundamentalist’ and ‘violent’ political movement,the inspiration for the present-day militant Muslim groups (like al-Qa`ida) in their struggle against modernity” (p. 30). The latter is an Egyptianreformer regarded as a liberal humanist who underlined the essence ofMuslim humanism for the modern world ...